Knowledge domain and emerging trends in HIV-MTB co-infection from 2017 to 2022: A scientometric analysis based on VOSviewer and CiteSpace - Miaona Liu; Wei Li; Wenmei Qiao; Limian Liang; Zhaoqin Wang (Frontiers Media S.A., 2023)
Co-infection with Mycobacterium tuberculosis (MTB) in human immunodeficiency virus (HIV)-infected individuals is one of the leading causes of death. Also, research on HIV and MTB (HIV-MTB) co-infection was found to have a downward trend. In this work, we performed the knowledge domain analysis and visualized the current research progress and emerging trends in HIV-MTB co-infection between 2017 and 2022 by using VOSviewer and CiteSpace. The relevant literatures in this article were collected in the Web of Science (WoS) database. VOSviewer and CiteSpace bibliometric software were applied to perform the analysis and visualization of scientific productivity and frontier. Among all the countries, USA was dominant in the field, followed by South Africa, and England. Among all the institutions, the University of Cape Town (South Africa) had more extensive collaborations with other research institutions. The Int J Tuberc Lung Dis was regarded as the foremost productive journal. Survival and mortality analysis, pathogenesis, epidemiological studies, diagnostic methods, prognosis improvement of quality of life, clinical studies and multiple infections (especially co-infection with COVID-19) resulted in the knowledge bases for HIV-MTB co-infection. The clinical research on HIV-MTB co-infection has gradually shifted from randomized controlled trials to open-label trials, while the cognition of HIV-TB has gradually shifted from cytokines to genetic polymorphisms. This scientometric study used quantitative and qualitative methods to conduct a comprehensive review of research on HIV-MTB co-infection published over the past 5 years, providing some useful references to further the study of HIV-MTB co-infection.